Integrated Treatment and Storage Solutions for Solid Radioactive Waste at the Russian Shipyard Near Polyarny - Griffith, A.; Engoy, T.; Endregard, M.; Busmundrud, O.; Schwab, P.; Nazarian, A.; Krumrine, P.; Backe, S.; Gorin, S.; Evans, B. (WM Symposia, Inc., 2002)
Russian Navy Yard No. 10 (Shkval), near the city of Murmansk, has been designated as the recipient for Solid Radioactive Waste (SRW) pretreatment and storage facilities under the Arctic Military Environmental Cooperation (AMEC) Program. This shipyard serves the Northern Fleet by servicing, repairing, and dismantling naval vessels. Specifically, seven nuclear submarines of the first and second generation and Victor class are laid up at this shipyard, awaiting defueling and dismantlement. One first generation nuclear submarine has already been dismantled there, but recently progress on dismantlement has slowed because all the available storage space is full. SRW has been placed in metal storage containers, which have been moved outside of the actual storage site, which increases the environmental risks. AMEC is a cooperative effort between the Russian Federation, Kingdom of Norway and the United States. AMEC Projects 1.3 and 1.4 specifically address waste treatment and storage issues. Various waste treatment options have been assessed, technologies selected, and now integrated facilities are being designed and constructed to address these problems. Treatment technologies that are being designed and constructed include a mobile pretreatment facility comprising waste assay, segregation, size reduction, compaction and repackaging operations. Waste storage technologies include metal and concrete containers, and lightweight modular storage buildings. This paper focuses on the problems and challenges that are and will be faced at the Polyarninsky Shipyard. Specifically, discussion of the waste quantities, types, and conditions and various site considerations versus the various technologies that are to be employed will be provided. A systems approach at the site is being proposed by the Russian partners, therefore integration with other ongoing and planned operations at the site will also be discussed.